Recent trends in cancer incidence in Nepal: A retrospective observational study - Rudra Prasad Khanal; Ishwar Koirala; Kanchan P Adhikari; Bidyapati Jha (Cancer Research, Statistics, and Treatment)
Background: Despite medical advancements, cancer remains a major global health challenge. In 2015, Nepal, with a population of 27 million, recorded 15,000-20,000 new cancer cases, with approximately 60% from low- and middle-income populations. Objectives: The primary objective was to identify high-burden districts for cancer in Nepal using hospital-based data. Secondary objectives included recommending targeted screening and promoting early detection programs in these regions. Materials and Methods: This retrospective observational study was conducted at the Department of Medical Physics, Bhaktapur Cancer Hospital, Bhaktapur. Records from 2003 to 2020 were reviewed, focusing on data from 2015 to 2020, with detailed analysis for 2018-2020. Descriptive statistics, line diagrams, and histograms were used to illustrate cancer trends by district, gender, and type. Results: From 2015 to 2020, five major hospitals in Nepal reported 57,486 new cancer cases (32,272 females, 25,214 males), with higher annual incidence in women in Chitwan and Morang. The most prevalent cancers were bronchus and lung (16.3%) in males and breast (16.9%) in females. Other frequent types included mouth, stomach, cervix, and lung cancers. While incidence and mortality were lower outside Kathmandu valley, both increased with age, particularly in those over 60. Conclusion: Chitwan and Morang reported the highest cancer burdens. Incidence rates rose again in 2020 after a dip in 2019. Strengthening early detection and prevention strategies in these high-risk districts is critical for effective cancer control in Nepal.